An organocatalytic method for constructing pyrroles via the cycloisomerisation of Z-1-iodo-4-N-methylbenzenesulfonyl-1, 6-enynes. Issue 33 (6th August 2019) - Meng, Long; Chi, Xiaochen; Sun, Xi; Cao, Chengqiang; Ai, Bing; Liu, Qing; Zhao, Pingping; Zhao, Zengdian; Dong, Yunhui; Liu, Hui
Abstract : A new cycloisomerisation of Z -1-iodo-4- N -methylbenzenesulfonyl-1, 6-enynes to functionalized pyrroles was realized in the presence of an organomolecule (4, 4′-bis(1, 1-dimethylethyl)-2, 2′-bipyridine) and KO t Bu. Abstract : A new cycloisomerisation of Z -1-iodo-4- N -methylbenzenesulfonyl-1, 6-enynes to functionalized pyrroles was realized in the presence of an organomolecule (4, 4′-bis(1, 1-dimethylethyl)-2, 2′-bipyridine) and KO t Bu. The transformations were performed efficiently to produce different kinds of functionalized pyrroles within 10 min. This is the first example of an organomolecule promoted methodology with vinyl iodides from a non-aromatic system to an aromatic system, which offers an excellent option toward establishing a new horizon for cross-coupling reactions of vinyl halides. Preliminary mechanistic studies were performed and a crude radical pathway was proposed.